-6=2(w-8)-7w

Simple and best practice solution for -6=2(w-8)-7w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=2(w-8)-7w equation:


Simplifying
-6 = 2(w + -8) + -7w

Reorder the terms:
-6 = 2(-8 + w) + -7w
-6 = (-8 * 2 + w * 2) + -7w
-6 = (-16 + 2w) + -7w

Combine like terms: 2w + -7w = -5w
-6 = -16 + -5w

Solving
-6 = -16 + -5w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '5w' to each side of the equation.
-6 + 5w = -16 + -5w + 5w

Combine like terms: -5w + 5w = 0
-6 + 5w = -16 + 0
-6 + 5w = -16

Add '6' to each side of the equation.
-6 + 6 + 5w = -16 + 6

Combine like terms: -6 + 6 = 0
0 + 5w = -16 + 6
5w = -16 + 6

Combine like terms: -16 + 6 = -10
5w = -10

Divide each side by '5'.
w = -2

Simplifying
w = -2

See similar equations:

| 4(5x+2)=40 | | 15x-(5x-4)=24 | | 40x+(8(1.5x))=640 | | 5(x+y)=3x+2y | | -15.4-3.5t=-(9.5t+0.4) | | -(6x-5y+4)= | | 5.1p-0.7(2+3p)=-10.4 | | 3/4y-6=1/4y+10 | | 28--4d=5d-17 | | 4+2(x-3)=20 | | 6x+6+2(9x-4)= | | 2b-3-10b-9= | | i(-i)= | | 0.25(8+4x)-0.5(10+2x)= | | 9w+w+8w= | | 3(x-1)+2(4x-5)=(x-3)+5 | | -2(7z+5)=-14z+13 | | 2sin^2x+3sinx+1=0 | | 3n^2-9n-3=0 | | -6w+19=8w+5 | | y+0.6y-1.2=2(y-1.4) | | -12x-14=-2(6x+7) | | h=-1+3l^2+s | | In(x-5)+In(x+6)=1 | | m^2+2mn-3n^2=0 | | X-3y=600 | | x^2+16x+64y^2=0 | | 5c+56=120 | | 9x+10=199 | | 128=3.14(8)(8)h | | 128=3.14(8)squaredh | | 3n+6-6=57-6 |

Equations solver categories